Rancang Bangun Media Pembelajaran Teknologi WAN Berbasis Android - Ulfa Isni Kurnia; Alfian Alfina; Fahlul Rizki (Fakultas Teknik Universitas Hamzanwadi, 2023)
The impact of the Covid-19 pandemic in the education sector is getting children used to using smartphones. Smartphones during a pandemic helped teachers deliver learning materials and became one of the learning media during the pandemic. Smartphones help teachers and students in the learning process during a pandemic. Learning media is a tool in the learning process. Learning helps teachers convey information in more interesting way. Current technological developments really help many people at work. In the education sector, technology can help in making learning media more interesting, for example by using the PowerPoint application in learning. This learning is made with an Android-based platform. Android-based learning media is learning media in the form of applications that are installed on smartphones and can be accessed directly by students. This Android-based learning media was developed using a prototyping model approach with the Adobe CS6 application. one of the functions of smartphones for teachers and students is as a learning medium. The benefits of Android-based learning media are that students can access it anywhere and anytime and support self-taught learning.